Evaluation of Rice Genotypes Resistance to Yellow Stem Borer, Scirpophaga incertulas (Walker) through Sex Pheromone Trap - Nyaupane, Sushil (Amrit Research Journal, 2022)
Yellow stem borer, Scirpophaga incertulas (Walker) is monophagous insect pest causing serious damage to rice growers of plain regions of Nepal. This study was done to evaluate the host preference of yellow stem borer to the various genotypes of rice. The research design employed was Randomized Complete Block Design (RCBD) with seven treatments and three replications and done in kharif season of 2021. Rice varieties selected were Sabitri, Sarju 52, US 312, Radha 4, Sawa Mansuli, Silki and Hardinath 3, which are popularly cultivated in Kailali. Sex pheromone trap (scirpolure) was installed to monitor the preference of yellow stem borer for various rice varieties, especially at the panicle initiation stage of rice. Statistical analysis of four weeks data of adult male moths trapped on different cultivars of rice revealed that the yellow stem borer adult moths were highly attracted to the US 312 and less attracted to Sarju 52 and Silki varieties. This research implied that the adoption of popular rice variety Sarju 52 could safeguard the farmers from the notorious pest i.e. yellow stem borer of rice.